2023
DOI: 10.3390/aerospace10020165
|View full text |Cite
|
Sign up to set email alerts
|

Design Exploration for Sustainable Regional Hybrid-Electric Aircraft: A Study Based on Technology Forecasts

Abstract: The environmental impact of aviation in terms of noise and pollutant emissions has gained public attention in the last few years. In addition, the foreseen financial benefits of an increased energy efficiency have motivated the transport industry to invest in propulsion alternatives. This work is collocated within the Clean Sky 2 project GENESIS, focused on the environmental sustainability of 50-passenger hybrid-electric aircraft from a life-cycle-based perspective to support the development of a technology ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…New secondary electric machines were designed based on nominal RPMs equal to 8000 since it was found that it is optimal to delegate to gearboxes the task of adapting the number of revolutions to that of the propellers. The specific fuel consumption reflects the usage of pure hydro-processed esters and fatty acids synthetic paraffinic kerosene (HEFA-SPK) as fuel [10].…”
Section: Fast-charging-stationsmentioning
confidence: 99%
See 1 more Smart Citation
“…New secondary electric machines were designed based on nominal RPMs equal to 8000 since it was found that it is optimal to delegate to gearboxes the task of adapting the number of revolutions to that of the propellers. The specific fuel consumption reflects the usage of pure hydro-processed esters and fatty acids synthetic paraffinic kerosene (HEFA-SPK) as fuel [10].…”
Section: Fast-charging-stationsmentioning
confidence: 99%
“…This paper is framed in the context of GENESIS, which corresponds to the EU theme JTI-CS2-2020-CFP11-THT-13 under the Clean Sky 2 programme for Horizon 2020 and presents a forward-looking view focusing on the assessment of appropriate energy supply technologies for ground energy storage, grid connection and power transmission to aircraft. Based on these technologies, a flight plan and the design of a 50 PAX HEA developed in the project, the energy requirements for operations at a regional airport can be estimated [10]. The fuel types for HEA change depending on the time horizon.…”
Section: Introductionmentioning
confidence: 99%
“…NASA is developing a battery powered electric airplane X-57 "Maxwell" with an innovative distributed propulsion system, which allows for a reduction in wing area, while providing the same lift with less motor power [40,8]. A similar distributed propulsion system is featured in the "ECO-150-300" [43] and the "DRAGON" [44] electric airplane models, as well as in the hybrid-electric plane design exploration in [36].…”
Section: Introductionmentioning
confidence: 99%
“…Aircraft fuel tanks house a substantial volume of aviation fuel, posing a significant threat to flight safety. As per records, 18 incidents of fuel tank explosions have occurred in transport aircraft, resulting in a total of 542 fatalities in the last 50 years [1][2][3]. In July 1996, 12 min after the take-off of Boeing 747 aircraft TWA800, the fuel vapor in the central wing fuel tank combusted and exploded, leading to the deaths of all 230 crew members [4][5][6].…”
Section: Introductionmentioning
confidence: 99%